The influence of leadership behaviours on talent retention: An empirical study - Michelle R. Mey; Paul Poisat; Carmen Stindt (SA Journal of Human Resource Management, 2021)
Orientation: Top talent remains the main source of organisational competitive advantage. The ability to attract, motivate and develop Talent management and retention of high performing employees is imperative for organisations to survive and thrive in today’s dynamic and volatile complex world of work. Studies reveal that employees’ intentions to stay or quit are influenced by the leadership behaviours of managers.